Thalamic Gating of Auditory Responses in Telencephalic Song Control Nuclei - Coleman, Melissa J. (J Neurosci, 2007)
In songbirds, nucleus Uvaeformis (Uva) is the sole thalamic input to the telencephalic nucleus HVC (used as a proper name), a sensorimotor structure essential to learned song production that also exhibits state-dependent responses to auditory presentation of the bird's own song (BOS). The role of Uva in influencing HVC auditory activity is unknown. Using in vivo extracellular and intracellular recordings in urethane-anesthetized zebra finches, we characterized the auditory properties of Uva and examined its influence on auditory activity in HVC and in the telencephalic nucleus interface (NIf), the main auditory afferent of HVC and a corecipient of Uva input. We found robust auditory activity in Uva and determined that Uva is innervated by the ventral nucleus of lateral lemniscus, an auditory brainstem component. Thus, Uva provides a direct linkage between the auditory brainstem and HVC. Although low-frequency electrical stimulation in Uva elicited short-latency depolarizing postsynaptic potentials in HVC neurons, reversibly silencing Uva exerted little effect on BOS-evoked activity in HVC neurons. However, high-frequency stimulation in Uva suppressed auditory-evoked synaptic and suprathreshold activity in all HVC neuron types, a process accompanied by decreased input resistance of individual HVC neurons. Furthermore, high-frequency stimulation in Uva simultaneously suppressed auditory activity in HVC and NIf. These results suggest that Uva can gate auditory responses in HVC through a mechanism that involves inhibition local to HVC as well as withdrawal of auditory-evoked excitatory drive from NIf. Thus, Uva could play an important role in state-dependent gating of auditory activity in telencephalic sensorimotor structures important to learned vocal control.